(untitled) (Journal of Nepal Geological Society, 2017)
This study analyzes the temporal trend of the Kahphuche glacier lake from 1990 to 2016 using multi-temporal satellite imagery to explore the glaciological causes of lake expansion. The Kahphuche glacial lake, has increased perceptibly in size over the last one and half decades, and it continues to expand. This study reveals that the glacial lake is not likely to burst in the near future as it is dammed by a 348 m wide moraine dam. However, the probability of a GLOF may occur if there is an avalanche or rock-fall, or seismic disturbance.